When you can’t see the city for the trees. A joint analysis of the Sonian Forest and urban reality - Lee Christopher Roland (Brussels Studies)
Considering the width of the Sonian Forest “ecotone”, the forest cannot be studied as “nature” which is independent of urban dynamics. In this part of the urban area, the distribution of forms of developed land did not take place in the form of isotropic rings moving outwards from a central area represented by the Pentagon, but rather according to a second element historically tied to the latter, i.e. the forest itself. This article presents a chronological overview of the relationships between the mass of plant life referred to as “the forest” and urban forms and the lifestyle practices associated with the Brussels urban area today. It first highlights the asymmetry created by the forest during the Ancien Régime in terms of the distribution of activities and developed land. It then reviews the role played by the forest in the processes of urbanisation in the south/southeast of Brussels in the 19th and 20th centuries. Finally, it explains the impact of these interactions on the construction of the forest landscape and on its management, before taking a stance with respect to how the forest should be dealt with today.